A randomised trial to investigate the effects of acute consumption of a blackcurrant juice drink on markers of vascular reactivity and bioavailability of anthocyanins in human subjects - Jin, Y; Alimbetov, D; George, T; Gordon, M H; Lovegrove, J A (European journal of clinical nutrition, 2011)
Background/Objectives: To study the bioavailability of anthocyanins and the effects of a 20% blackcurrant juice drink on vascular reactivity, plasma antioxidant status and other cardiovascular disease risk markers. Subjects/Methods: The study was a randomised, cross-over, double-blind, placebo-controlled acute meal study. Twenty healthy volunteers (11 females and 9 males) were recruited, and all subjects completed the study. Fasted volunteers consumed a 20% blackcurrant juice drink (250 ml) or a control drink following a low-flavonoid diet for the previous 72 h. Vascular reactivity was assessed at baseline and 120 min after juice consumption by laser Doppler imaging (LDI). Plasma and urine samples were collected periodically over an 8-h period for analysis, with a final urine sample collected at 24 h. The cross-over was performed after a 4-week washout. Results: There were no significant effects of the 20% blackcurrant juice drink on acute measures of vascular reactivity, biomarkers of endothelial function or lipid risk factors. Consumption of the test juice caused increases in plasma vitamin C ( P= 0.006), and urinary anthocyanins ( P <0.001). Delphinidin-3-rutinoside and cyanidin-3-rutinoside were the main anthocyanins excreted in urine with delphinidin-3-glucoside also detected. The yield of anthocyanins in urine was 0.021±0.003% of the dietary intake of delphinidin glycosides and 0.009±0.002% of the dietary intake of cyanidin glycosides. Conclusions: The juice consumption did not have a significant effect on vascular reactivity. Anthocyanins were present at low concentrations in the urine, and microbial metabolites of flavonoids were detected in plasma after juice consumption.